Role of Vitamin D Status in Diabetic Patients with Renal Disease - Guido Gembillo; Valeria Cernaro; Antonino Salvo; Rossella Siligato; Alfredo Laudani; Michele Buemi; Domenico Santoro (Medicina, 2019)
Diabetes mellitus (DM) poses a major public health problem worldwide, with ever-increasing incidence and prevalence in recent years. The Institute for Alternative Futures (IAF) expects that the total number of people with type 1 and type 2 DM in the United States will increase by 54%, from 19,629,000 to 54,913,000 people, between 2015 and 2030. Diabetic Nephropathy (DN) affects about one-third of patients with DM and currently ranks as the first cause of end-stage kidney disease in the Western world. The complexity of interactions of Vitamin D is directly related with progressive long-term changes implicated in the worsening of renal function. These changes result in a dysregulation of the vitamin D-dependent pathways. Various studies demonstrated a pivotal role of Vitamin D supplementation in regression of albuminuria and glomerulosclerosis, contrasting the increase of glomerular basement membrane thickening and podocyte effacement, with better renal and cardiovascular outcomes. The homeostasis and regulation of the nephron’s function are absolutely dependent from the cross-talk between endothelium and podocytes. Even if growing evidence proves that vitamin D may have antiproteinuric, anti-inflammatory and renoprotective effects in patients with DN, it is still worth investigating these aspects with both more in vitro studies and randomized controlled trials in larger patient series and with adequate follow-up to confirm the effects of long-term vitamin D analogue supplementation in DN and to evaluate the effectiveness of this therapy and the appropriate dosage.